Morphology of two species of the thecate dinoflagellate genus Blepharocysta (Dinophyta) from the tropical Mexican Pacific - David Uriel Hernández-Becerril; Graciela Arce-Rocha (Revista Mexicana de Biodiversidad)
The genus Blepharocysta Ehrenberg currently comprises 5 species of truly marine planktonic thecate dinoflagellates, which are solitary, globose, subspherical and heterotrophic cells, lack typical depressed cingulum and sulcus, and are mainly distributed in tropical areas. The morphology of 2 species, Blepharocysta splendor-maris and B. paulsenii, found in net samples from the tropical Mexican Pacific, was studied by LM and SEM, especially plate arrangement and theca ornamentation. Blepharocysta splendor-maris showed more ovoid cells, developed sulcal lists, and theca with shallow poroids having a relative low density, whereas B. paulsenii had more spherical cells, shorter epitheca, reduced and slightly ornamented sulcal lists, and theca with deep poroids having a relatively higher density. The thecal tabulation in both species agrees with conventional tabulation, including the anterior intercalary plate in B. paulsenii. A comparison of both morphological and ecological characteristics among all species of the genus is done, outstanding shape of cells, relative size, development of sulcal lists, and especially the theca ornamentation as important morphological characters to distinguish species. Blepharocysta splendor-maris is the only species distributed from tropical to Antarctic waters, whereas the others are limited to tropical and subtropical waters.